Modern approaches to choosing growth strategies for companies - Skopenko, Nataliya; Severyna, Iryna (Herald of Economics, 2025)
Introduction. In today’s business environment, characterized by high market volatility and increasing risks, companies are compelled to seek new paths for development. Economic, political, and social transformations – particularly those driven by military events – necessitate business adaptation to emerging challenges. In response to these changes, enterprises are increasingly shifting from organic growth strategies to inorganic ones, particularly through mergers and acquisitions (M&A), as a way to strengthen competitive advantages and respond promptly to external environmental shifts.Purpose of the study. This study aims to identify the specifics of organic and inorganic company growth, to analyze their strengths and weaknesses, and to determine the feasibility of applying appropriate development strategies under current conditions.Research methods. This study employs both general scientific and specialized methods. System analysis methods were used to examine information regarding the development status of Ukrainian companies; comparative analysis was applied to distinguish between organic and inorganic growth strategies; generalization methods helped identify the key negative factors affecting business operations in recent years; tabular methods were used to visualize the research findings.Results. The study found that organic growth enables gradual company development through the use of internal resources and competencies, although it is limited in terms of scale and dynamics. Inorganic growth, on the other hand, is based on integration processes, mergers, and partnerships, which allow for rapid business expansion but involve higher costs and risks. For Ukrainian companies operating in conditions of war and economic instability, inorganic approaches and restructuring are particularly relevant as tools for stabilization. The choice of an optimal strategy should be based on an assessment of internal resources, investment capacity, industry specifics, and external factors, which together shape an individual development trajectory for each enterprise.Prospects. The prospects for further exploration lie in the need for systematic monitoring of changes in the external environment, enabling timely adjustments to business development strategies and ensuring sustainable competitive positions in the market.